MATHEMATICAL MODEL OF CHEMICAL PROCESSES OCCURRING IN ELECTRIC ARC FURNACES (Computer systems and information technologies, 2021)
The article provides a mathematical model of chemical processes occurring in electric arc furnace (EAF). The authors of the article are the first to build up a new algorithm of calculating the main characteristics of chemical processes taking place in EAF. This algorithm is notable for its simplicity and convenience of execution and helps to calculate the mass of substances entering into a chemical reaction and its products, the quantity of heat emitted or absorbed. So, it would be reasonable to use the algorithm described in this article while creating complex models of EAF, in particular, while studying the thermal and chemical processes occurring in the furnace and looking for their correlation, while constructing energy and material balance of EAF. Besides, due to the high level of calculations that are performed with the help of this algorithm, it is convenient to use it while formulating the laws of optimal management of EAF. Its adequacy is proved by comparison of the calculations to the experimental data.